Dr. Jekyll and Mr. Hyde Revisited. (2nd October 2022) - Merritt, Dennis; Lu, Kevin; Merritt, Frazer
Abstract : The publication of Robert Lewis Stevenson's The Strange Case of Dr. Jekyll and Mr. Hyde in January of 1886 created a shock wave in the consciousness of its readers. It was an instant success in and beyond the literary world as people were confronted with the uneasy thought that evil originated within the individual and not from an external source like the Devil. This was nine years before Freud conducted his first psychoanalysis, and decades before Jung introduced the concept of the shadow. Stevenson was known as the author of Treasure Island and children's poetry, but had long been looking for a vehicle to write about the strange "Other" he had been aware of since his childhood nightmares. The inspiration for Jekyll and Hyde came directly from a dream, and he attributed most of his literary success to help from the "Brownies, " the "little people, " in his interior world and dreamland. The novel can be viewed in relation to the love-hate relationship with his father, whom he depended upon for financial support during his lifelong struggles with severe respiratory illness, which led to drug addiction from his attempts to cope with the illness. For Stevenson, the Other was primarily the dark side of the strict Calvinistic religion of his father and proper late 19th century Scottish culture, yet the concept is even more relevant today as we face the evils of terrorism, racism, white-collar crime, Putin and rising authoritarianism, and intolerable levels of polarization in many modern societies.